Antigen-Independent Restriction of Pneumococcal Density by Mucosal Adjuvant Cholera Toxin Subunit B. (24th April 2016) - Kuipers, Kirsten; Diavatopoulos, Dimitri A.; van Opzeeland, Fred; Simonetti, Elles; van den Kieboom, Corné H.; Kerstholt, Mariska; Borczyk, Malgorzata; van IngenSchenau, D.; Brandsma, Eelke T.; Netea, Mihai G.; de Jonge, Marien I.
Abstract: For many bacterial respiratory infections, development of (severe) disease is preceded by asymptomatic colonization of the upper airways. For Streptococcus pneumoniae, the transition to severe lower respiratory tract infection is associated with an increase in nasopharyngeal colonization density. Insight into how the mucosal immune system restricts colonization may provide new strategies to prevent clinical symptoms. Several studies have provided indirect evidence that the mucosal adjuvant cholera toxin subunit B (CTB) may confer nonspecific protection against respiratory infections. Here, we show that CTB reduces the pneumococcal load in the nasopharynx, which required activation of the caspase-1/11 inflammasome, mucosal T cells, and macrophages. Our findings suggest that CTB-dependent activation of the local innate response synergizes with noncognate T cells to restrict bacterial load. Our study not only provides insight into the immunological components required for containment and clearance of pneumococcal carriage, but also highlights an important yet often understudied aspect of adjuvants.